2015
DOI: 10.1371/journal.pone.0130055
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analysis and Experimental Validation of Lignan Extracts from Kadsura longipedunculata for Potential 5-HT1AR Agonists

Abstract: Objectives Kadsura longipedunculata (KL) has been widely used for the treatment of insomnia in traditional Chinese medicine. The aim of this study was to explore the mechanism of the sedative and hypnotic effects of KL.Materials and MethodsThe content of KL was evaluated by HPLC-TOF-MS, and a potential target was found and used to construct its 3D structure to screen for potential ligands among the compounds in KL by using bioinformatics analysis, including similarity ensemble approach (SEA) docking, homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Notably, a number of following docking studies reported in literature described a unique receptor cavity involved in the 5-HT 1A full agonists, partial agonists and antagonists binding [58][59][60], giving a further validation to our previous computational findings. Indeed, H-bond interactions between agonists and D116 and N386 were reported in literature, falling in a crevice delimited by F112, I113, D116, K191, while partial agonists as well as antagonists were Hbonded at least with D116.…”
Section: -Ht 1a R Docking-studiessupporting
confidence: 86%
“…Notably, a number of following docking studies reported in literature described a unique receptor cavity involved in the 5-HT 1A full agonists, partial agonists and antagonists binding [58][59][60], giving a further validation to our previous computational findings. Indeed, H-bond interactions between agonists and D116 and N386 were reported in literature, falling in a crevice delimited by F112, I113, D116, K191, while partial agonists as well as antagonists were Hbonded at least with D116.…”
Section: -Ht 1a R Docking-studiessupporting
confidence: 86%
“…We then utilized the SEA database (Zheng et al. 2015 ) for determining targets of the MHT compounds. Here, to predict potential targets of MHT, we used a similarity-based method, the core idea of which is to rank potential compound-target interactions based on their similarity to known compound-target interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Additional studies were aimed to conduct docking in 5HT receptors 5HT 1a , 5HT 2a e 5HT 3 . To reach this goal, the amino acid sequence of 5HT 1a was downloaded from UniProt database (accession code: P08908, 5HT1A_HUMAN) and the 3D structure of 5-HT1AR was constructed using the SWISS-MODEL server according to Zheng et al (2015) [ 38 ]. 5HT 2a receptor was similarly built from 5HT 2b and the amino acid sequence of 5HT 2a Uniprot database (accession code: P28223) according to Gandhimathi and Sowdhamini, (2015) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%